On the facilitative effects of face motion on face recognition and its development - Xiao, Naiqi G.; Perrotta, Steve; Quinn, Paul C.; Wang, Zhe; Sun, Yu-Hao P.; Lee, Kang (Frontiers in Psychology, 2014)
For the past century, researchers have extensively studied human face processing and its development. These studies have advanced our understanding of not only face processing, but also visual processing in general. However, most of what we know about face processing was investigated using static face images as stimuli. Therefore, an important question arises: to what extent does our understanding of static face processing generalize to face processing in real-life contexts in which faces are mostly moving? The present article addresses this question by examining recent studies on moving face processing to uncover the influence of facial movements on face processing and its development. First, we describe evidence on facial movements’ facilitation effect on face recognition and two related theoretical hypotheses: the supplementary information hypothesis and the representation enhancement hypothesis. We then highlight several recent studies suggesting that facial movements optimize face processing by activating specific face processing strategies that accommodate to task requirements. Lastly, we review the influence of facial movements on the development of face processing in the first year of life. We focus on infants’ sensitivity to facial movements and explore the facilitative effects of facial movements on infants’ face recognition performance. We conclude by outlining several future directions in investigating moving face processing and emphasize the importance of including dynamic aspects of facial information to further understand face processing in real-life contexts.